Efektivitas Senam Hamil dalam Mengurangi Nyeri Punggung Bawah pada Ibu Hamil Trimester II dan III di Puskesmas Kuta Baro Kabupaten Aceh Besar - Risna Fazlaini; Donny Hendra; Zaitun Zaitun; Ummu Aiman; Salamah Salamah (Teewan Journal Solutions, 2026)
Background: According to the World Health Organization (WHO), the prevalence of low back pain during pregnancy is approximately 70% in Australia. Similarly, in Indonesia, low back pain is one of the most frequently reported discomforts during pregnancy, with approximately 70% of pregnant women experiencing this condition in the late stages of pregnancy. Low back pain is a pain syndrome occurring in the lower back region as a result of the anterior shift in the body's center of gravity during pregnancy. This condition commonly affects pregnant women and may interfere with their daily activities and overall quality of life. Regular participation in prenatal exercise during the last trimester of pregnancy has been shown to reduce pain experienced during labor compared with women who do not participate in such exercise. This study aimed to determine the effect of prenatal exercise on reducing low back pain among pregnant women in the second and third trimesters at Kuta Baro Community Health Center. Methods: This study employed a pre-experimental research design using a one-group pretest–posttest approach. A total of 44 pregnant women participated in the study. Data were analyzed using univariate and bivariate analyses, with hypothesis testing performed using the Paired Sample t-test. Results: The findings demonstrated that prenatal exercise had a statistically significant effect on reducing low back pain among pregnant women in the second and third trimesters at Kuta Baro Community Health Center, Aceh Besar Regency, in 2026 (p-value < 0.001). Conclusion: Prenatal exercise significantly reduced low back pain among pregnant women in the second and third trimesters at Kuta Baro Community Health Center, Aceh Besar Regency. Recommendation: Prenatal exercise is recommended as a safe and effective non-pharmacological intervention for managing low back pain during pregnancy. Therefore, pregnant women, particularly those in the second and third trimesters, are encouraged to participate in regular prenatal exercise programs to improve